Exploration of broadly neutralizing antibody fragments produced in bacteria for the control of HIV. Issue 11 (2nd November 2017) - Lloyd, Sarah B.; Niven, Keith P.; Kiefel, Ben R.; Montefiori, David C.; Reynaldi, Arnold; Davenport, Miles P.; Kent, Stephen J.; Winnall, Wendy R.
ABSTRACT: While broadly neutralizing antibodies (bnAbs) are a promising preventative and therapeutic tool for HIV infection, production is difficult and expensive. Production of antibody-like fragments in bacterial cytoplasm provides a cheaper alternative. This work explored the transplantation of the complementarity determining regions of the anti-HIV bnAbs PGT121 and 10E8 onto a single-chain variable fragment (scFv) scaffold, previously discovered through a novel screening platform. The scaffolded 10E8 scFv, but not the scaffolded PGT121 scFv, was soluble in bacterial cytoplasm, enabling efficient production in bacteria. Three additional multimeric constructs employing the scaffolded 10E8 scFv were also generated and soluble versions produced in bacteria. However, the constructs were found to have substantially lost anti-HIV binding function and had completely abrogated neutralizing activity. Overall, while this study provides a proof-of-concept for anti-HIV bnAb construct production in bacterial cytoplasm, future refinement of these technologies will be required to realize the goal of producing inexpensive and effective bnAb-like tools for the control of HIV.